A Study of Various Challenges of Big Data: Exploring the Challenges and Solutions of Big Data (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Massive, quick and various knowledge moving quickly all over making what is referred to as “Big Data” era. This knowledge becomes vital source for valuable insights and ultimately serving to create a lot of informed call. But this knowledge with terribly special attributes can’t be managed and processed by these ancient computer code systems, That became a true drawback. This study can discuss all different challenges of huge knowledge classified into 3 main groups Data, method and management challenges. Knowledge challenges are the cluster of the challenges relates to the characteristics of the information itself. Method cluster includes all the challenges encountered whereas processing the massive Data started with capture step and finished with presenting the output to purchasers